Gender differences with the use of percutaneous left ventricular assist device in cardiogenic shock patients – results from the Dresden Impella Registry. (3rd October 2022) - Mierke, J; Nowack, T; Loehn, T; Poege, F; Schuster, M C; Woitek, F; Haussig, S; Ibrahim, K; Pfluecke, C; Mangner, N; Linke, A
Abstract: Background: Cardiogenic shock (CS) is a state of end-organ hypoperfusion due to cardiac output failure and is characterized by high mortality. Percutaneous left ventricular assist devices (pLVAD), like the Impella® system, support the left ventricular function and provide a sufficient oxygen supply to all tissues, which might improve outcome. In the current study, we investigated gender-specific differences in a large, propensity score matched cohort of patients receiving an Impella CP® in CS. Beside all-cause mortality, we focused on requirement of hemodialysis and surrogate parameters like development of systemic inflammatory response syndrome (SIRS), or sepsis, which is known to be associated with enhanced morbidity and mortality. Methods: The Dresden Impella Registry is an ongoing registry including more than 650 patients since 2014. Among, a total of 95 female and 237 male patients received an Impella CP® in CS. Two groups of similar sample size (n=60) resulted after propensity score matching. A logistic regression model was used for adjustment of the baseline characteristics (nearest neighbor matching). Kaplan-Meier curves at 30, 180 and 365 days as well as clinical, laboratory and hemodynamic parameters were compared between male and female patients. Results: The propensity score matched cohorts showed a well balancing without significant differences between baseline characteristics. At time of admission, female patients were 68.9±1.8 years old, male patients 67.2±1.5 years. A cardiopulmonary resuscitation (CPR) before pLVAD was performed in 53.3% in both groups. The comparison of mean arterial pressure, norepinephrine and dobutamine dosage showed no differences initially and in course. The left ventricular ejection fraction did not differ between both cohorts (♀ 28.6±2.3% vs. ♂ 26.7±1.7%, p=0.885). The duration of left ventricular unloading was 44.1±6.5 h among female patients and 56.0±7.3 h among male patients (p=0.119). The all-cause mortality showed no difference at 30, 180, and 365 d (30 d: ♀ 61.7±6.3% vs. ♂ 56.7±6.4%, p=0.349; 180 d: ♀ 73.3±5.7% vs. ♂ 68.3±6.0%, p=0.312; 365 d: ♀ 76.7±5.5% vs. ♂ 70.0±5.9%, p=0.312). However, hemodialysis was less frequently required in female patients (♀ 28.3% vs. ♂ 45.8%, p=0.049). The duration of hemodialysis did not differ between the groups (♀ 123.9±57.8 h vs. ♂ 108.1±56.3 h, p=0.744). Furthermore, occurrence of SIRS and sepsis were less frequently observed in female patients (SIRS ♀ 45.0% vs. ♂ 75.0%, p=0.042; sepsis ♀ 43.3% vs. ♂ 62.7%, p=0.034). Conclusion: All-cause mortality showed no gender-specific differences in a well-balanced propensity score matched analysis of CS patients receiving LV-unloading with a pLVAD. However, females had a decreased requirement of hemodialysis and a less frequent occurrence of SIRS and sepsis. Further studies are needed to investigate whether these differences might improve outcome in larger cohorts. Funding Acknowledgement: Type of funding sources: None.